Calidad de vida del paciente con epilepsia en el Centro Neurológico Sánchez - Loaiza Guzhñay, Paola del Cisne (2020)
Epilepsy is a disease that affects both the cultural and socioeconomic fields and is important for the development of the patient's life, requiring knowledge of their quality of life, since in many parts of the world they can be victims of stigmatization and discrimination. The patient with epilepsy in addition to the disease, faces negative circumstances such as side effects of some medications, fear of the unexpected appearance of crises and limitations in daily activities. The objective of this project was to determine the quality of life of patients with epilepsy who come to the Sánchez Neurological Center in the city of Loja in the period January - December 2018 and relate it to both sex and the age group. This is a descriptive study in which the QOLIE-10 questionnaire was applied, obtaining the following results: the patients studied were a total of 53, of which 60.4% (n=32) correspond to the male sex, according 28.3% (n=15) belong to the 16 to 20 age group. By applying the QOLIE-10 questionnaire, it was obtained that the quality of life in 56.6% (n=30) is very good for both the female and male sex, in 30.2% (n=16) good, in 9.4% (n=5) fair and both excellent and poor in 1.9% (n=1). Finally, it was concluded that the quality of life that prevails in epileptic patients is very good, despite all kinds of stigmatization that currently continues to appear. Key words: QOLIE-10, stigmatization, discrimination.